2009
DOI: 10.1007/s00247-009-1272-z
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of the small bowel in children with idiopathic inflammatory bowel disease: evaluation of disease activity

Abstract: This MR imaging protocol is a safe and well-tolerated method for evaluating disease activity and extraintestinal manifestations of IBD in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 28 publications
2
22
0
3
Order By: Relevance
“…Nevertheless, the combination of ADC values and perfusion parameters makes it possible to improve specificity. In their study of children with chronic inflammatory bowel disease, Alexopoulou et al showed that the percentage-based enhancement of the intestinal wall was significantly higher in patients with abnormal C-reactive protein (CRP) values, i. e. with acute inflammation parameters, than in patients with normal CRP values [51]. DCE-MRI requires contrast medium administration within a strictly defined timeframe to allow the quantitative and qualitative analysis of time-signal- Fig.…”
Section: Dynamic Contrast Enhanced (Dce) Mrimentioning
confidence: 99%
“…Nevertheless, the combination of ADC values and perfusion parameters makes it possible to improve specificity. In their study of children with chronic inflammatory bowel disease, Alexopoulou et al showed that the percentage-based enhancement of the intestinal wall was significantly higher in patients with abnormal C-reactive protein (CRP) values, i. e. with acute inflammation parameters, than in patients with normal CRP values [51]. DCE-MRI requires contrast medium administration within a strictly defined timeframe to allow the quantitative and qualitative analysis of time-signal- Fig.…”
Section: Dynamic Contrast Enhanced (Dce) Mrimentioning
confidence: 99%
“…This was crucial to obtain a valid dataset in an objective manner for further scrutiny. To our knowledge, there are few studies in the literature on MR imaging of the small bowel in the pediatric population (15)(16)(17)(18)(19). Laghi et al (15) correlated clinical disease activity with contrast enhancement and wall thickening on MRI, whereas, the Alexopoulou group (16) only used contrast enhancement.…”
Section: Correlation Between Clinical and Radiological Findingsmentioning
confidence: 99%
“…Meanwhile, other studies have demonstrated a correlation between MRE and CDAI (33,46,47) and a correlation between MRE and laboratory markers of inflammation (erythrocyte sedimentation rate/C-reactive protein) (41-43). Only two pediatric studies compared MRE to PCDAI, one demonstrating a statistically significant correlation between disease on MRE and PCDAI (48) and the other demonstrating no correlation between MRE and PCDAI (49).…”
Section: Comparison Of Mre To Disease Activity Indexmentioning
confidence: 99%